Calcium Phosphate Coatings with Controlled Micro/Nano-Structures for Endothelial Cells Viability - Adil Elrayah; Ke Duan; Xiong Lu; Xiaob Lu; Jie Weng (Journal of Techniques, 2024)
Hydroxyapatite (HA) scaffolds produced by the accumulation of HA fibers were separately treated hydrothermally in three calcium phosphate solutions to form coatings of different micro/nano-structures. Different micro/nano-structure and morphologies have been regulated on the surface of treated HA scaffolds. Plate-like compromise flower-like morphology was obtained with solution 1 (Ca-sufficient) i.e., ratio: Ca/Ca=1%; Ca/P=1.67. Full coatings (flower-like) morphology treated after Cu-doped coating solution 2 (Cu/(Cu+Ca) = 5%; ratio: (Cu+Ca)/P = 1.67). Furthermore, partial coatings (flower-like) morphology fabricated with solution 3 (Ca-deficient and Cu-replacement), i.e., ratio: Ca/Ca=0.95%; Ca/P=1.58. The results showed the effect of hydrothermal coatings on HA scaffolds. Cultured human endothelial cells spread and proliferated better on the treated HA scaffolds than on the uncoated scaffolds, suggesting a potential effect of calcium phosphate surface morphology on endothelial cell response. Thus, it can provide an appropriate micro/nano-structure approach supporting angiogenesis capacity, which is a necessity to accelerate the time of bone healing and regeneration.